2002
DOI: 10.1269/jrr.43.247
|View full text |Cite
|
Sign up to set email alerts
|

Relative Biological Effectiveness of 290 MeV/u Carbon Ions for the Growth Delay of a Radioresistant Murine Fibrosarcoma

Abstract: The relative biological effectiveness (RBE) for animal tumors treated with fractionated doses of 290 MeV/u carbon ions was studied. The growth delay of NFSa fibrosarcoma in mice was investigated following various daily doses given with carbon ions or those given with cesium gamma-rays, and the RBE was determined. Animal tumors were irradiated with carbon ions of various LET (linear energy transfer) in a 6-cm SOBP (spread-out Bragg peak), and the isoeffect doses; i.e. the dose necessary to induce a tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…This finding is in agreement with a previous report that heavy-ion irradiation inhibits in vitro angiogenesis (29). Several previous studies reported that the in vivo RBE values for high LET carbon-ion beams ranged from 2.0 to 3.1 (30,31). In the present study, the in vivo RBE was calculated as 3.05 to 3.25 from the slope of the dose-response curve for tumor growth suppression by carbon ions relative to X-rays, which is almost in line with previous reports (30,31).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in agreement with a previous report that heavy-ion irradiation inhibits in vitro angiogenesis (29). Several previous studies reported that the in vivo RBE values for high LET carbon-ion beams ranged from 2.0 to 3.1 (30,31). In the present study, the in vivo RBE was calculated as 3.05 to 3.25 from the slope of the dose-response curve for tumor growth suppression by carbon ions relative to X-rays, which is almost in line with previous reports (30,31).…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies reported that the in vivo RBE values for high LET carbon-ion beams ranged from 2.0 to 3.1 (30,31). In the present study, the in vivo RBE was calculated as 3.05 to 3.25 from the slope of the dose-response curve for tumor growth suppression by carbon ions relative to X-rays, which is almost in line with previous reports (30,31). It is known that RBE is a complex quantity, depending on many factors such as particle type, dose per fraction, and LET, as well as on biological factors like cell or tissue type and the selected biological endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the tumor growth time for the treatment group and for a nonirradiated control group was defined as the tumor growth delay. 36 Tumor growth delay induced by radiation treatment was used as a parameter to measure treatment effect.…”
Section: Original Article 5084mentioning
confidence: 99%
“…It is assumed that the RBE systematics found for in vitro and in vivo also remain true for clinical data, thus permitting the use of these estimates as surrogate of the 'clinical RBE' to predict the clinical treatment outcome. Following the linear-quadratic (LQ) formalism, the initial RBE (α/α X ) after ion beam irradiation mainly depends on the α X /β X ratio for the reference radiation (Koike et al 2002, Friedrich et al 2012b. The reduction of the required input information to the α X /β X ratios also increases the range of applicability, since this ratio is known for many tumor and normal tissues.…”
Section: Introductionmentioning
confidence: 99%